THE SUBJECTIVE FACTORS IMPACT ON CONFLICT DYNAMICS (Security Dialogues, 2024)
Regardless of the level at which they occur, ie. from the lowest individual or local, up to the highest or global one, conflicts usually attract the most attention, when aggression and violence become a part of the conflict behavior. At the same time, in such situations the focus of all involved actors (direct and indirect) in the conflict is usually placed on the objective causes and aspects that have initiated the violence occurrence or escalation. It practically means that the importance of subjective aspects and factors for such conflict situations, is often put on the margins in conflict management approaches. Starting from the thesis that such aspects, above all: perceptions, stereotypes and the interpretation of past experience, also have a significant impact on the conflict constellation and structure, the paper analyzes their mutual relationship more specifically. Actually, behind the objective and visible values and assumptions about a concrete conflict, there are almost always in the background, other, deeper values and assumptions (perceptions, stereotypes, prejudices) that further complicate its nature and structure. Hence, the paper analyzes the essential characteristics of theseaspects, especially through the prism of their impact on the conflict dynamics expansion and complication. The purpose of such an analysis is to advance the awareness about the meaning and impact of subjective aspects on the conflict, as well as the awareness about the need for apply a broader and multidisciplinary approaches in dealing with conflicts.
Keywords: conflict, perceptions, stereotypes, past experience, resolution